Refining lake volume estimation and critical depth identification for enhanced glacial lake outburst flood (GLOF) event anticipation - Bazai, N.; Carling, P.; Cui, P.; Hao, W.; Guotao, Z.; Liu, D.; Hassan, J. (The Cryosphere, 2024)
Climate change leads to changes in glacier mass balance, including steady advancements and surges that reposition the glacier snouts. Glacier advancement can dam proglacial meltwater lakes. Within the Karakoram and surrounding regions, the positive feedback of climate change has resulted in more frequent ice-dammed glacial lake outburst floods (GLOFs), often facilitated by englacial conduits. However, the complex and multi-factor processes of conduit development are difficult to measure. Determining the lake depths that might trigger GLOFs and the numerical model specifications for breaching is challenging. Empirical estimates of lake volumes, along with field-based monitoring of lake levels and depths and the assessment of GLOF hazards, enable warnings and damage mitigation. Using historical data, remote sensing techniques, high-resolution imagery, cross-correlation feature tracking, and field-based data, we identified the processes of lake formation, drainage timing, and triggering depth. We developed empirical approaches to determine lake volume and trigger water pressure leading to a GLOF. A correlation, albeit a weak one, between glacier surge velocity and lake volume reveals that glacier surge may play a crucial role in lake formation and thus controls the size and volume of the lake. Lake volume estimation involves geometric considerations of the lake basin shape. A GLOF becomes likely when the lake's normalized depth (n′) exceeds 0.60, equivalent to a typical water pressure on the dam face of 510 kPa. These field and remotely sensed findings not only offer valuable insights for early warning procedures in the Karakoram but also suggest that similar approaches might be effectively applied to other mountain environments worldwide where GLOFs pose a hazard.